Composite particles for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

JP7644731B2Active Publication Date: 2025-03-12SAMSUNG SDI CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022059554
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-03-12
Estimated Expiration
2042-03-31

AI Technical Summary

Benefits of technology

【0023】 本発明に係る非水電解質二次電池用複合粒子によれば、50℃~250℃の吸熱量が150J/g以上500J/g以下であり、ホスホン酸による修飾度が適切な範囲に設定されている。そのため、この複合粒子を含有する非水電解質二次電池の内部温度の上昇を、例えば内部短絡など電池の異常により内部温度が上昇しやすい環境下においても十分に抑制することができる。 その結果、非水電解質二次電池の内部温度の上昇によって引き起こされる電池の劣化を抑えて、非水電解質二次電池のサイクル寿命を向上させることができる。 さらに、前記複合粒子の体積抵抗率が0.10Ωcm以上4×104Ωcm以下であることによって、前記複合粒子を吸熱性だけでなく導電助剤としての性質をも有する吸熱性導電助剤とすることができる。 その結果、本発明に係る複合粒子を正極や負極に含有させた場合であっても非水電解質二次電池の電気抵抗を小さく抑えることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644731000003
    Figure 0007644731000003
  • Figure 0007644731000001
    Figure 0007644731000001
  • Figure 0007644731000002
    Figure 0007644731000002
Patent Text Reader

Abstract

To provide composite particles for a nonaqueous electrolyte secondary battery that can sufficiently suppress the increase of inside temperature of the nonaqueous electrolyte secondary battery even under environments where the inside temperature tends to rise such as high temperature environments and can suppress the electrical resistance of the nonaqueous electrolyte secondary battery to a low level.SOLUTION: The composite particles for a nonaqueous electrolyte secondary battery contain metal hydroxide particles and conductive particles. The volume resistivity at 60 MPa pressure is 0.10 Ω cm or more and 4×104 Ω cm or less. The endothermic value measured by a differential scanning calorimetry at 50°C to 250°C is 150 J / g or more and 500 J / g or less. The amount of desorbed P2 (MS1) at 80 to 1400°C measured by a thermal desorption spectroscopy mass spectrometry (TDS-MS) is 300×10-6 mol / g or more and 3000×10-6 mol / g or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite particles for non-aqueous electrolyte secondary batteries and non-aqueous electrolyte secondary batteries. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, including lithium-ion secondary batteries, are widely used as power sources for devices such as smartphones and laptop computers, and more recently have also been used as large batteries for vehicles. On the other hand, while lithium ion secondary batteries have the advantage of high energy density, they require sufficient safety measures because of the use of a non-aqueous electrolyte. In recent years, as batteries have become larger, ensuring safety has become even more important.

[0003] For example, when a lithium-ion secondary battery is placed in a high-temperature environment, the positive electrode of the lithium-ion secondary battery may generate heat, causing an increase in the internal temperature of the battery. When the internal temperature becomes high, the separator of the lithium-ion secondary battery may shrink, causing a short circuit. As a result, there is a risk of causing a further increase in the internal temperature.

[0004] Therefore, in order to ensure the safety of lithium-ion secondary batteries, it has been proposed to contain heat-absorbing particles, which are inorganic particles made of a metal hydroxide having heat absorption properties, in the lithium-ion secondary battery to suppress the rise in internal temperature.

[0005] For example, Patent Document 1 describes a method of improving the safety of a battery by disposing endothermic particles, which are inorganic particles made of endothermic and basic calcium silicate or the like, having a specific surface area ratio due to water vapor and nitrogen gas adsorption of 0.45 or more and less than 2.0, in a separator.

[0006] Furthermore, References 2 and 3 each describe the inclusion of aluminum hydroxide particles having a maximum endothermic peak temperature of 270°C or more and 360°C or less in DSC and a dehydration reaction temperature range of 200°C or more and 400°C or less in the electrolyte or separator. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6925368 [Patent Document 2] JP 2016-162528 A [Patent Document 3] Patent No. 4364940 Summary of the Invention [Problem to be solved by the invention]

[0008] However, according to the studies of the present inventors, it has been found that the inorganic particles described in Patent Document 1 may not be able to sufficiently suppress the internal temperature of the non-aqueous electrolyte secondary battery.

[0009] Furthermore, in the temperature ranges described in References 2 and 3, the separator included in the nonaqueous electrolyte secondary battery melts and the charged positive electrode decomposes.

[0010] Furthermore, when inorganic particles as described in Patent Documents 1 to 3 are contained in the positive electrode or negative electrode of a nonaqueous electrolyte secondary battery, there is a problem that the volume resistivity of these inorganic particles is high, resulting in high electrical resistance of the nonaqueous electrolyte secondary battery as a whole.

[0011] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide heat-absorbing particles that can suppress an increase in the internal temperature of a non-aqueous electrolyte secondary battery even in an environment in which the internal temperature is likely to increase due to an abnormality in the battery, such as an internal short circuit, and further can keep the electrical resistance of the non-aqueous electrolyte secondary battery low. [Means for solving the problem]

[0012] That is, the composite particles for a non-aqueous electrolyte secondary battery according to the present invention are composite particles containing metal hydroxide particles and conductive particles, Volume resistivity at 60 MPa is 0.10 Ωcm or more 4×10 4 Ωcm or less, The endothermic heat amount at 50°C to 250°C in differential scanning calorimetry is 150 J / g or more and 500 J / g or less, The amount of desorbed P2 (MS1) from 80 to 1400°C measured by a temperature programmed desorption gas mass spectrometer (TDS-MS) was 300×10 -6 mol / g or more 3000×10 -6 It is characterized in that it is mol / g or less.

[0013] According to the composite particles for nonaqueous electrolyte secondary batteries thus configured, the degree of modification with phosphonic acid, which is determined by the amount of P2 gas desorbed, is set within an appropriate range, so that an increase in the internal temperature of a nonaqueous electrolyte secondary battery containing these composite particles can be sufficiently suppressed.

[0014] In addition, the volume resistivity of this composite particle when pressurized at 60 MPa is 0.10 Ωcm or more (4×10 4 Since the electrical resistance is Ωcm or less, even when the composite particles are contained in the positive electrode and / or negative electrode, the electrical resistance of the nonaqueous electrolyte secondary battery can be kept low.

[0015] The amount of H2O desorbed from the composite particles at 80 to 200 °C (MS2) was 100 × 10 -6 mol / g or more 1500×10 -6 It is preferable that the desorbed gas amount ratio (MS1 / MS2) satisfies the following formula (1). 0.5≦(MS1 / MS2)≦5.0 (1)

[0016] The composite particles have a diameter of 1350 cm as measured by Raman spectroscopy. -1 The area of ​​the peak near D ) and 1580cm -1 The area of ​​the peak near G ) ratio (A D / A G ) is 0.5 or more and 3.5 or less, 2680cm measured by Raman spectroscopy -1 Peak half-width (G'-FWHM) around 60cm -1 More than 150cm -1 It is preferable that:

[0017] The composite particles have a specific surface area (BET1) of 8 m2 calculated based on an adsorption isotherm measured by adsorbing water vapor. 2 / g or more 600m 2 / g or less, The specific surface area (BET2) of the composite particles calculated based on the adsorption isotherm measured by adsorbing nitrogen is 10 m 2 / g or more 600m 2 It is preferable that the molecular weight is not more than 1 / g.

[0018] It is preferable that the ratio of the specific surface areas (BET1 / BET2) satisfies the following formula (2). 0.2≦(BET1 / BET2)≦5.0 (2)

[0019] The amount of CH4 desorbed from the composite particles at temperatures between 80 and 1400°C (MS3) was 30×10 -6 mol / g or more 1000×10 -6 mol / g or less, The amount of CH3OH desorbed from 80 to 1400℃ by TDS-MS (MS4) was 10×10 -6 mol / g or more 3000×10 -6 It is preferably mol / g or less.

[0020] The amount of C6H6 desorbed from the composite particles at temperatures between 80 and 1400°C (MS5) was 1×10 -6 mol / g or more 4000×10 -6 It is preferably mol / g or less.

[0021] In a specific embodiment of the present invention, the metal hydroxide is at least one selected from the group consisting of aluminum hydroxide, pseudoboehmite, boehmite, alumina, and kaolinite.

[0022] The present invention also includes a positive electrode or a negative electrode for a nonaqueous electrolyte secondary battery containing the above-mentioned composite particles for nonaqueous electrolyte batteries in an amount of 0.1% by weight or more and 5.0% by weight or less, and a nonaqueous electrolyte secondary battery including such a positive electrode or negative electrode. Effect of the Invention

[0023] According to the composite particles for non-aqueous electrolyte secondary batteries of the present invention, the heat absorption amount at 50° C. to 250° C. is 150 J / g or more and 500 J / g or less, and the degree of modification with phosphonic acid is set within an appropriate range. Therefore, the rise in the internal temperature of a non-aqueous electrolyte secondary battery containing the composite particles can be sufficiently suppressed even in an environment where the internal temperature is likely to rise due to an abnormality in the battery, such as an internal short circuit. As a result, deterioration of the battery caused by an increase in the internal temperature of the nonaqueous electrolyte secondary battery can be suppressed, and the cycle life of the nonaqueous electrolyte secondary battery can be improved. Furthermore, the volume resistivity of the composite particles is 0.10 Ωcm or more and 4×10 4 By having a resistivity of Ωcm or less, the composite particles can be made into an endothermic conductive assistant having not only heat absorption but also properties as a conductive assistant. As a result, even when the composite particles according to the present invention are contained in the positive electrode or negative electrode, the electrical resistance of the non-aqueous electrolyte secondary battery can be kept low. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a schematic diagram showing the structure of a composite particle according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] A specific configuration of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention will be described below. <1. Basic structure of non-aqueous electrolyte secondary battery> The nonaqueous electrolyte secondary battery according to this embodiment is a lithium ion secondary battery including a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte. The shape of the lithium ion secondary battery is not particularly limited, but may be, for example, any of a cylindrical shape, a rectangular shape, a laminate shape, a button shape, and the like.

[0026] (1-1. Positive electrode) The positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector. The positive electrode current collector may be any conductive material, for example, a plate or foil, and is preferably made of aluminum, stainless steel, nickel-plated steel, or the like. The positive electrode mixture layer contains at least a positive electrode active material, and may further contain a conductive agent and a positive electrode binder.

[0027] The positive electrode active material is, for example, a transition metal oxide or solid solution oxide containing lithium, and is not particularly limited as long as it is a material that can electrochemically absorb and release lithium ions. Examples of the transition metal oxide containing lithium include Li 1.0 Ni 0.88 Co 0.1 Al 0.01 Mg 0.01 O2, etc., but also LiCoO2 and other Li·Co-based composite oxides, LiNi x Co y Mn z Examples of the solid solution oxide include Li·Ni·Co·Mn-based composite oxides such as LiO2, Li·Ni-based composite oxides such as LiNiO2, and Li·Mn-based composite oxides such as LiMn2O4. a Mn x Co y Ni z O2 (1.150≦a≦1.430, 0.45≦x≦0.6, 0.10≦y≦0.15, 0.20≦z≦0.28), LiMn 1.5 Ni0.5 Examples of the positive electrode active material include O4 and the like. The content (content ratio) of the positive electrode active material is not particularly limited, and may be any content that is applicable to the positive electrode mixture layer of the non-aqueous electrolyte secondary battery. These compounds may be used alone or in combination.

[0028] The conductive agent is not particularly limited as long as it is capable of increasing the conductivity of the positive electrode. Specific examples of the conductive agent include those containing one or more selected from carbon black, natural graphite, artificial graphite, fibrous carbon, and sheet carbon. Examples of the carbon black include furnace black, channel black, thermal black, ketjen black, and acetylene black. Examples of the fibrous carbon include carbon nanotubes and carbon nanofibers, and examples of the sheet-like carbon include graphene. The content of the conductive agent in the positive electrode mixture layer is not particularly limited, but from the viewpoint of achieving both electrical conductivity and battery capacity, the content is preferably 0.1 mass % or more and 5 mass % or less, and more preferably 0.5 mass % or more and 3 mass % or less, based on the entire positive electrode mixture layer.

[0029] Examples of the positive electrode binder include fluorine-containing resins such as polyvinylidene fluoride, ethylene-containing resins such as styrene-butadiene rubber, ethylene-propylene-diene terpolymer, acrylonitrile-butadiene rubber, fluororubber, polyvinyl acetate, polymethylmethacrylate, polyethylene, polyvinyl alcohol, carboxymethyl cellulose or carboxymethyl cellulose derivatives (salts of carboxymethyl cellulose, etc.), or nitrocellulose. The positive electrode binder is not particularly limited as long as it can bind the positive electrode active material and the conductive agent onto the positive electrode current collector.

[0030] (1-2. Negative electrode) The negative electrode includes a negative electrode current collector and a negative electrode mixture layer formed on the negative electrode current collector. The negative electrode current collector may be any conductive material, and is preferably, for example, in the form of a plate or foil, and is made of copper, stainless steel, nickel-plated steel, or the like.

[0031] The negative electrode mixture layer contains at least a negative electrode active material, and may further contain a conductive agent and a negative electrode binder. The negative electrode active material is not particularly limited as long as it can electrochemically absorb and release lithium ions. Examples of the negative electrode active material include graphite active materials (artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, etc.), Si-based active materials or Sn-based active materials (for example, a mixture of fine particles of silicon (Si) or tin (Sn) or an oxide thereof and a graphite active material, fine particles of silicon or tin, and an alloy based on silicon or tin), metallic lithium, and Li4Ti5O 12 Examples of the negative electrode active material include titanium oxide compounds such as lithium nitride and lithium carbide. As the negative electrode active material, one of the above may be used, or two or more of them may be used in combination. The oxide of silicon is represented by SiOx (0≦x≦2).

[0032] The conductive agent is not particularly limited as long as it is capable of increasing the conductivity of the negative electrode, and for example, the same conductive agent as that described in the section regarding the positive electrode can be used. The content of the conductive agent in the negative electrode mixture layer is not particularly limited, but from the viewpoint of achieving both electrical conductivity and battery capacity, the content is preferably 0.1 mass % or more and 5 mass % or less, and more preferably 0.5 mass % or more and 3 mass % or less, based on the entire negative electrode mixture layer.

[0033] The negative electrode binder is not particularly limited as long as it can bind the negative electrode active material and the conductive agent on the negative electrode current collector. The negative electrode binder may be, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), styrene butadiene copolymer (SBR), metal salt of carboxymethyl cellulose (CMC), etc. One type of binder may be used alone, or two or more types may be used.

[0034] (1-3. Separator) The separator is not particularly limited, and may be any separator that can be used as a separator for a lithium ion secondary battery. As the separator, it is preferable to use a porous membrane or a nonwoven fabric that exhibits excellent high-rate discharge performance, either alone or in combination. Examples of resins constituting the separator include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyvinylidene difluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene difluoride-perfluorovinyl ether copolymer, vinylidene difluoride-tetrafluoroethylene copolymer, vinylidene difluoride-trifluoroethylene copolymer, vinylidene difluoride- ... copolymer, vinylidene difluoride-hexafluoroacetone copolymer, vinylidene difluoride-ethylene copolymer, vinylidene difluoride-propylene copolymer, vinylidene difluoride-trifluoropropylene copolymerExamples of the separator include vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene difluoride-tetrafluoroethylene copolymer, vinylidene difluoride-ethylene-tetrafluoroethylene copolymer, etc. The porosity of the separator is not particularly limited, and the porosity of the separator of a conventional lithium ion secondary battery can be arbitrarily applied.

[0035] The separator may further include a surface layer that covers the surface of the porous membrane or nonwoven fabric. The surface layer may include an adhesive for bonding with the electrodes to fix the battery element. Examples of the adhesive include vinylidene fluoride-hexafluoropropylene copolymer, an acid-modified vinylidene fluoride polymer, and a styrene-(meth)acrylic acid ester copolymer.

[0036] (1-4.Non-aqueous electrolyte) The nonaqueous electrolyte may be the same as the nonaqueous electrolyte conventionally used in lithium ion secondary batteries, without any particular limitation. The nonaqueous electrolyte has a composition in which an electrolyte salt is contained in a nonaqueous solvent, which is a solvent for the electrolyte. Examples of the non-aqueous solvent include cyclic carbonates such as propylene carbonate, ethylene carbonate, butylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, and vinylene carbonate; cyclic esters such as γ-butyrolactone and γ-valerolactone; chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethylmethyl carbonate; methylformate, methylacetate, methylbutyrate, ethyl propionate, and propyl propionate. propionate, tetrahydrofuran or its derivatives, 1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, 1,4-dibutoxyethane (1,4-dibutoxyethane, methyldiglyme, ethers such as ethylene glycol monopropyl ether, propylene glycol monopropyl ether, nitriles such as acetonitrile, benzonitrile, dioxolane or a derivative thereof, ethylene sulfide, sulfolane, sultone or a derivative thereof, etc., can be used alone or in combination of two or more kinds. When two or more kinds of the nonaqueous solvents are used in combination, the mixing ratio of the nonaqueous solvents can be the same as that used in conventional lithium ion secondary batteries.

[0037] Examples of electrolyte salts include LiClO4, LiBF4, LiAsF6, LiPF6, and LIPF6-x (C n F 2n+1 )x[However, 1 <x<6、n=1or2]、LiSCN、LiBr、LiI、Li2SO4、Li2B 10 Cl 10, NaClO4, NaI, NaSCN, NaBr, KClO4, KSCN and other inorganic ion salts containing one of lithium (Li), sodium (Na) or potassium (K), LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiC(C2F5SO2)3, (CH3)4NBF4, (CH3)4NBr, (C2H5)4NClO4, (C2H5)4NI, (C3H7)4NBr, (n-C4H9)4NClO4, (n-C4H9)4NI, (C2H5)4N-maleate, (C2H5)4N-benzoate, (C2H5)4N-phtalate, lithium stearyl sulfonic acid Examples of suitable ionic compounds include organic ionic salts such as lithium, octyl sulfonic acid lithium, and dodecyl benzenesulfonic acid lithium. These ionic compounds can be used alone or in combination of two or more. The concentration of the electrolyte salt may be the same as that of the non-aqueous electrolyte used in conventional lithium ion secondary batteries, and is not particularly limited. In this embodiment, it is preferable to use a non-aqueous electrolyte containing the above-mentioned lithium compound (electrolyte salt) at a concentration of about 0.8 mol / L or more and 1.5 mol / L or less.

[0038] In addition, various additives may be added to the non-aqueous electrolyte. Examples of such additives include negative electrode additives, positive electrode additives, ester additives, carbonate additives, sulfate additives, phosphate additives, borate additives, acid anhydride additives, and electrolyte additives. Any one of these may be added to the non-aqueous electrolyte, or multiple types of additives may be added to the non-aqueous electrolyte.

[0039] 2. Characteristics and configuration of the nonaqueous electrolyte secondary battery according to the present embodiment The characteristic configuration of the nonaqueous electrolyte secondary battery according to this embodiment will be described below. The positive electrode mixture layer of the nonaqueous electrolyte secondary battery according to this embodiment contains, in addition to the above-mentioned components, composite particles that function as a heat-absorbing conductive assistant for nonaqueous electrolyte secondary batteries.

[0040] The composite particles are composite particles in which metal hydroxide particles capable of absorbing heat by endothermic reaction and conductive particles having electrical conductivity are composited. As shown in FIG. 1, the composite particles are composite particles in which the metal hydroxide particles and the conductive particles are mixed as uniformly as possible. Here, the composite refers to a state in which a plurality of particles are chemically bonded to each other via functional groups (e.g., carboxyl groups and hydroxyl groups) possessed by each particle to form a single mass. The chemical bond here includes not only the covalent bond as described above, but also various bonds such as ionic bonds, coordinate bonds, and metallic bonds. The bond state between the particles can be confirmed, for example, by X-ray photoelectron spectroscopy.

[0041] The metal hydroxide particles are not particularly limited as long as they can cause an endothermic reaction. Specific examples of the metal hydroxide include aluminum hydroxide, pseudoboehmite, boehmite, alumina, and kaolinite. These may be used alone or in combination of two or more.

[0042] The average primary particle size of the metal hydroxide particles is preferably 10 nm or more and 20 μm or less, and more preferably 50 nm or more and 10 μm or less.

[0043] The conductive particles are not particularly limited as long as they are conductive. Specific examples of materials constituting the conductive particles include carbon materials and metal nanoparticles. Examples of the metal nanoparticles include gold nanoparticles, silver nanoparticles, and copper nanoparticles. The carbon material may include one or more selected from carbon black, natural graphite, artificial graphite, fibrous carbon, and sheet-like carbon. Examples of the carbon black include furnace black, channel black, thermal black, ketjen black, and acetylene black. Examples of the fibrous carbon include single-walled carbon nanotubes and multi-walled carbon nanotubes, and examples of the sheet-like carbon include graphene.

[0044] The composite particles contain the conductive particles as described above, and thus have a 1350 cm -1 The area of ​​the peak near D ) and 1580cm -1 The area of ​​the peak near G ) ratio (A D / A G ) is 0.5 to 3.5, and the 2680 cm -1 Peak half-width (G'-FWHM) around 60cm -1 More than 150cm -1 It is preferable that the content is in the following range:

[0045] The conductive particles preferably have an average primary particle size or fiber length of 1 nm to 10 μm, more preferably 10 nm to 1 μm. When metal nanoparticles are used as the conductive particles, any particle size can be used as long as the average primary particle size is on the nm order, but it is preferable that the average primary particle size is, for example, 1 nm to 500 nm.

[0046] The content of hydroxide particles in the composite particles is preferably in the range of 1% by mass or more and 60% by mass or less, more preferably in the range of 5% by mass or more and 50% by mass or less, and even more preferably in the range of 10% by mass or more and 40% by mass or less, based on the total mass of the composite particles.

[0047] The content of the conductive particles in the composite particles is preferably in the range of 0.1% by mass or more and 25% by mass or less, more preferably in the range of 0.5% by mass or more and 20% by mass or less, and even more preferably in the range of 1% by mass or more and 15% by mass or less, based on the total weight of the composite particles.

[0048] The composite particles have a specific surface area and a degree of modification with various modifying groups within the following ranges.

[0049] The specific surface area (BET1) calculated based on the adsorption isotherm measured by adsorbing water vapor onto the composite particles is 8m 2 / g or more 600m 2 / g or less, and the specific surface area (BET2) of the composite particles calculated from an adsorption isotherm measured by adsorbing nitrogen to the composite particles is 8 m 2 / g or more 600m 2 / g or less.

[0050] BET1 is 10m 2 / g or more 300m 2 / g or less, and 2 / g or more 100m 2 It is more preferable that the molecular weight is not more than 1 / g. BET2 is 9m 2 / g or more 300m 2 / g or less, and 2 / g or more 100m 2 It is more preferable that the molecular weight is not more than 1 / g. The specific surface area ratio (BET1 / BET2), which is the ratio between BET1 and BET2, is preferably 0.2 or more and 5.0 or less, more preferably 0.5 or more and 4.0 or less, and particularly preferably 1.0 or more and 3.0 or less.

[0051] In addition, the amount of P2 gas desorbed from the composite particles when the composite particles were heated from 80° C. to 1400° C. was measured by TDS-MS, and the amount of desorbed P2 (referred to as MS1) was 300×10 -6 mol / g or more 3000×10 -6mol / g or less. The amount of P2 released (M1) is an index showing the degree of modification of the composite particle with phosphonic acid. The amount of H2O desorbed from the composite particles when heated from 80° C. to 1400° C. is preferably 30×10-6 mol / g or more and 1500×10-6 mol / g or less when measured by TDS-MS (MS2). This amount of H2O desorbed is a reference value for the degree of modification of the composite particles, and the ratio of these gas desorbed amounts (M1 / M2) is preferably 0.5 or more and 5.0 or less, more preferably 1.0 or more and 4.0 or less, and particularly preferably 1.5 or more and 3.0 or less.

[0052] In order to further improve the heat absorbing effect of the composite particles, it is preferable that the composite particles are modified with functional groups such as CH3 groups, CH2OH groups, etc. The degree of modification with these functional groups can be evaluated by the amount of desorption of the following various gases derived from these functional groups, similar to the degree of modification with phosphonic acid, and it is preferable that the amount of desorption of the various gases satisfies the following ranges. The amount of CH4 gas desorbed from the composite particles when the composite particles were heated from 80°C to 1400°C was measured by TDS-MS, and the amount of desorbed CH4 (referred to as MS3) was 30 x 10 -6 mol / g or more 1000×10 -6 mol / g or less, and the amount of CH3OH released (MS4) measured in the same manner is 10 x 10 -6 mol / g or more 1000×10 -6 It is preferably mol / g or less.

[0053] MS3 is 50×10 -6 mol / g or more and 300×10 -6 mol / g or less is more preferable, and 60×10 -6 mol / g or more and 250×10 -6 It is particularly preferable that the amount is mol / g or less. MS4 is 20×10 -6 mol / g or more and 2000×10 -6mol / g or less, and 25×10 -6 mol / g or more and 1900×10 -6 It is particularly preferable that the amount is mol / g or less.

[0054] When the composite particles are modified with a functional group containing a phenyl group, the metal hydroxide particles can be easily dispersed in a solvent when preparing a slurry such as a positive electrode mixture slurry. Therefore, the amount of C6H6 desorbed from the metal hydroxide particles at 80°C to 1400°C by TDS-MS (referred to as MS5) was 1 x 10 -6 mol / g or more 4000×10 -6 mol / g or less, and preferably 2×10-6 mol / g or more and 2000×10 -6 mol / g or less is more preferable, and 3×10 -6 mol / g or more 1600×10 -6 It is particularly preferable that the amount is mol / g or less.

[0055] The total content of the modifying molecules in the composite particle is preferably in the range of 10% by mass or more and 90% by mass or less, more preferably in the range of 20% by mass or more and 80% by mass or less, and even more preferably in the range of 30% by mass or more and 70% by mass or less, relative to 100% by mass of the entire composite particle.

[0056] The heat absorption by the composite particles realized by the surface area and degree of modification with various modifying groups as described above is preferably such that the heat absorption amount at 50°C to 250°C in differential scanning calorimetry is 150 J / g or more and 500 J / g or less, more preferably 170 J / g or more and 5400 J / g or less, and particularly preferably 180 J / g or more and 300 J / g or less.

[0057] Even when the composite particles are contained in a positive electrode mixture layer or a negative electrode mixture layer, in order to minimize the decrease in conductivity, the volume resistivity of the composite particles when pressurized at 60 MPa is set to 0.1 Ωcm or more and 4×10 4 The volume resistivity is set to be 0.3 Ωcm or more and 3.8×10 4It is preferable that the resistivity is 0.5Ωcm or more and 3.6×10 4 It is more preferable that the resistivity is Ωcm or less.

[0058] The content of the composite particles in the positive electrode mixture layer is preferably in the range of 0.1 mass% or more and 5 mass% or less, more preferably 0.2 mass% or more and 3 mass% or less, and particularly preferably 0.5 mass% or more and 2 mass% or less, based on the entire positive electrode mixture layer. Furthermore, the content of the composite particles for non-aqueous electrolyte secondary batteries in the entire non-aqueous electrolyte secondary battery varies depending on the application of the non-aqueous electrolyte secondary battery and is not limited to the following range; however, for example, when the mass of the entire non-aqueous electrolyte secondary battery is taken as 100 mass%, the content of the composite particles for non-aqueous electrolyte secondary batteries contained in the non-aqueous electrolyte secondary battery is preferably 0.01 mass% or more and 5.0 mass% or less, more preferably 0.02 mass% or more and 2.0 mass% or less, and particularly preferably 0.1 mass% or more and 0.5 mass% or less.

[0059] <3. Method for manufacturing the nonaqueous electrolyte secondary battery according to the present embodiment> Next, a method for manufacturing the lithium ion secondary battery according to this embodiment will be described. (3-1. Method for producing composite particles) The composite particles for a non-aqueous electrolyte secondary battery according to this embodiment can be produced by first producing composite particles 1 of metal hydroxide particles and conductive particles, and then modifying the composite particles. The composite particles can be obtained by first mixing and heating a metal nitrate, which is the raw material for the metal hydroxide, with conductive particles, and drying the mixture to produce metal hydroxide particles and at the same time form composite particles in which the metal hydroxide particles and conductive particles are combined. The heating temperature is preferably 80°C or higher and 200°C or lower, and more preferably 120°C or higher and 180°C or lower.

[0060] As a method for heating and mixing the metal hydroxide raw material and the conductive particles, for example, a method using a spray dryer can be mentioned. By using this spray dryer, composite particles in which the metal hydroxide particles and the conductive particles are combined as uniformly as possible can be obtained, so it is preferable to use a spray dryer for producing the composite particles. The composite particles may be modified, for example, by immersing the composite particles in a modifying treatment agent for a predetermined period of time.

[0061] Examples of the modifying agent include phosphoric acid, phosphonic acid, and phosphinic acid. The treatment time for modifying the composite particles can be appropriately changed depending on the type and concentration of the treatment agent, but is preferably from 30 minutes to 48 hours, and more preferably from 1 hour to 30 hours. The treatment temperature can also be appropriately selected depending on the type and concentration of the treatment agent, but is preferably 30°C or higher and 90°C or lower, and more preferably 40°C or higher and 80°C or lower.

[0062] (3-2. Method for producing positive electrode) The positive electrode is produced as follows. First, a positive electrode active material, a conductive agent, a positive electrode binder, and the composite particles are mixed in a desired ratio and dispersed in a positive electrode slurry solvent to form a positive electrode slurry. Next, the positive electrode slurry is applied onto a positive electrode current collector and dried to form a positive electrode mixture layer. The application method is not particularly limited. Examples of the application method include a knife coater method, a gravure coater method, a reverse roll coater, and a slit die coater. The following application steps are also performed in the same manner. Next, the positive electrode mixture layer is pressed to a desired density by a press machine. This produces a positive electrode.

[0063] (3-3. Method for producing negative electrode) The negative electrode is also prepared in the same manner as the positive electrode. First, a mixture of materials constituting the negative electrode mixture layer is dispersed in a solvent for the negative electrode slurry to prepare a negative electrode slurry. Next, the negative electrode slurry is applied onto a negative electrode current collector and dried to form a negative electrode mixture layer. Next, the negative electrode mixture layer is pressed by a press machine to a desired density. This completes the negative electrode.

[0064] (3-4. Method for manufacturing non-aqueous electrolyte secondary battery) Next, the separator is sandwiched between the positive and negative electrodes to produce an electrode structure. The electrode structure is then processed into a desired shape (e.g., cylindrical, rectangular, laminated, button, etc.) and inserted into a container of the desired shape. Next, a nonaqueous electrolyte is injected into the container, so that the electrolyte is impregnated into each pore in the separator and the gaps in the positive and negative electrodes. This completes the production of a lithium ion secondary battery.

[0065] 4. Effects of this embodiment With the nonaqueous electrolyte secondary battery configured as described above, even in an environment in which the internal temperature is likely to rise due to a battery abnormality such as an internal short circuit, an increase in the internal temperature of the nonaqueous electrolyte secondary battery can be sufficiently suppressed, and further, the electrical resistance of the nonaqueous electrolyte secondary battery can be kept low.

[0066] <5. Other embodiments of the present invention> The present invention is not limited to the above-described embodiment. In the above embodiment, the positive electrode contains the composite particles according to the present invention, but the negative electrode may contain the composite particles. When the negative electrode contains the composite particles, it is preferable that the content of the composite particles is the same as that of the positive electrode. The composite particles may be contained in the electrolyte, or may be contained in a plurality of locations among the positive electrode, the negative electrode, and the electrolyte. When the negative electrode contains the composite particles for a non-aqueous electrolyte secondary battery, the content of the composite particles for a non-aqueous electrolyte secondary battery relative to the entire negative electrode is preferably in the same range as that of the positive electrode.When the electrolytic solution contains the composite particles for a non-aqueous electrolyte secondary battery, the content of the composite particles for a non-aqueous electrolyte secondary battery is preferably in the range of 0.1% by weight to 10.0% by weight, based on the mass of the entire electrolytic solution being 100% by mass. Needless to say, the present invention is not limited to these embodiments, and various modifications are possible without departing from the spirit of the present invention. EXAMPLES

[0067] The present invention will be described in more detail below with reference to specific examples. However, the following examples are merely examples of the present invention, and the present invention is not limited to the following examples.

[0068] [Preparation of heat-absorbing particles] <Preparation of heat-absorbing particles> (Examples 1 to 4, Comparative Example 4) 50.0 g of aluminum nitrate nonahydrate and 5.0 g of acetylene black were dispersed in 250 cc of ethanol. This dispersion was spray-dried at 150°C using a spray dryer manufactured by GF Co., Ltd. to obtain composite particles A' (BET1: 344 m) before modification in which aluminum hydroxide particles and acetylene black particles were bonded. 2 / g, BET2:1.2m 2 / g) was obtained.

[0069] (Examples 5 and 7) 50.0 g of aluminum nitrate nonahydrate and 25.0 g of acetylene black were dispersed in 250 cc of ethanol. This dispersion was spray-dried at 150°C using a spray dryer manufactured by GF Co., Ltd. to obtain composite particles B' (BET1: 344 m) before modification in which aluminum hydroxide particles and acetylene black particles were bonded. 2 / g, BET2:1.2m 2 / g) was obtained.

[0070] Example 6 50.0 g of aluminum nitrate nonahydrate and 1.0 g of acetylene black were dispersed in 250 cc of ethanol. This dispersion was spray-dried at 150°C using a spray dryer manufactured by GF Co., Ltd. to obtain composite particles C' (BET1: 344 m) before modification in which aluminum hydroxide particles and acetylene black particles were bonded. 2 / g, BET2: 1.2m 2 / g) was obtained.

[0071] <Modification of heat absorbing particles> Example 1 1.0 g of unmodified composite particles A' and 3.0 g of phosphoric acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1). This dispersion was heated at 80°C for 4 hours and then vacuum dried to obtain modified composite particles A.

[0072] Example 2 Modified composite particles B were obtained by the same procedure as in Example 1, except that 1.0 g of pre-modified composite particles A' and 3.0 g of ethylphosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1).

[0073] Example 3 Modified composite particles C were obtained by the same procedure as in Example 1, except that 1.0 g of pre-modified composite particles A' and 3.0 g of phenylphosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1).

[0074] Example 4 Modified composite particles D were obtained by the same procedure as in Example 1, except that 1.0 g of pre-modified composite particles A' and 3.0 g of diphenylphosphinic acid were dispersed in 50 cc of a mixed solution of ethanol and toluene (mixing ratio 1:1).

[0075] Example 5 Modified composite particles E were obtained by the same procedure as in Example 1, except that 1.0 g of pre-modified composite particles B' and 3.0 g of phenylphosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1).

[0076] Example 6 Modified composite particles F were obtained by the same procedure as in Example 1, except that 1.0 g of pre-modified composite particles C' and 5.0 g of phenylphosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1).

[0077] Comparative Example 6 Pseudo-boehmite (BET1:407m 2 / g, BET2:377m 2 Modified pseudoboehmite particles were obtained in the same manner as in Example 1, except that 1.0 g of phenylphosphonic acid (1.0 g / g) and 3.0 g of phenylphosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1).

[0078] <Preparation of a mixture of heat absorbing particles and conductive particles> Comparative Example 7 10.0 g of the modified pseudoboehmite particles of Comparative Example 6 and 10.0 g of acetylene black were mixed for 10 minutes in a V-type mixer manufactured by Dalton Co., Ltd. to obtain a particle mixture a.

[0079] Comparative Example 8 20.0 g of the modified pseudoboehmite particles of Comparative Example 6 and 10.0 g of acetylene black were mixed for 10 minutes in a V-type mixer manufactured by Dalton Co., Ltd. to obtain a particle mixture b.

[0080] Comparative Example 9 10.0 g of the modified pseudoboehmite particles of Comparative Example 6 and 30.0 g of acetylene black were mixed for 10 minutes in a V-type mixer manufactured by Dalton Co., Ltd. to obtain a particle mixture c.

[0081] Comparative Example 10 Pseudoboehmite particles (BET1: 407m 2 / g, BET2:377m 2 10.0 g of cellulose acetate / g and 10.0 g of acetylene black were mixed for 10 minutes in a V-type mixer manufactured by Dalton Co., Ltd. to obtain a particle mixture d.

[0082] [Positive electrode production] (Examples 1-6, Comparative Examples 2-10) LiCoO2, acetylene black, polyvinylidene fluoride, and endothermic particles were dispersed and mixed in a mass ratio of 97.0:1.0:1.3:0.7 as dry powder in N-methyl-2-pyrrolidone solvent to prepare a positive electrode mixture slurry. Then, the mixture coating amount (areal density) after drying was 20.0 mg / cm on one side. 2 The slurry was applied to one side of an aluminum current collector foil so that the density of the mixture layer became 4.15 g / cc, and then the mixture was pressed with a roll press machine so that the density of the mixture layer became 4.15 g / cc to prepare a positive electrode.

[0083] (Comparative Example 1, Example 7) LiCoO 2 A positive electrode was produced in the same manner as in Example 1, except that the positive electrode mixture slurry was produced by dispersing and mixing the powders of acetylene, acetylene black, and polyvinylidene fluoride in a mass ratio of 97.7:1.0:1.3 as dry powders in N-methyl-2-pyrrolidone solvent.

[0084] [Negative electrode production] (Examples 1-6, Comparative Examples 1-10) The negative electrode mixture slurry was prepared by dissolving and dispersing the artificial graphite, carboxymethylcellulose sodium salt (CMC), and styrene butadiene-based water dispersion in a mass ratio of 97.5:1.0:1.5 as dry powder in an aqueous solvent. Then, the mixture coating amount (areal density) after drying was 10.5 mg / cm. 2 The negative electrode mixture slurry was applied to one side of a copper foil and dried, and then pressed with a roll press machine so that the mixture layer density became 1.65 g / cc to prepare a negative electrode.

[0085] Example 7 A negative electrode was produced in the same manner as in Example 1, except that the artificial graphite, carboxymethylcellulose sodium salt (CMC), styrene-butadiene-based water dispersion, and composite particle E of Example 5 were dissolved and dispersed in an aqueous solvent in a mass ratio of 96.5:1.0:1.5:1.0 as dry powders to produce a negative electrode mixture slurry.

[0086] [Secondary battery cell production] (Examples 1-7, Comparative Examples 1-10) An electrode laminate was prepared by laminating a plurality of positive and negative electrodes with a polypropylene porous separator interposed therebetween so that the battery design capacity was 300 mAh. Next, nickel and aluminum lead wires were welded to the negative and positive electrodes of the electrode laminate in an aluminum laminate film, respectively, and then the electrode laminate was stored with the lead wires pulled out to the outside, and an electrolyte was poured and sealed under reduced pressure to prepare a secondary battery cell before initial charging. The electrolyte used was a solvent mixture of ethylene carbonate / dimethyl carbonate / fluoroethylene carbonate in a ratio of 15 / 80 / 5 (volume ratio) in which 1.3 M LiPF6 and 1% by mass of vinylene carbonate were dissolved.

[0087] [Evaluation of heat-absorbing particles] The endothermic particles used in the examples and comparative examples were evaluated as follows. <Specific surface area of ​​heat absorbing particles (BET)> The specific surface area (BET, which is the specific surface area calculated based on the adsorption isotherm measured by adsorbing water vapor) of inorganic particles or composite particles was measured using a gas adsorption measurement device (BELSORP, manufactured by Microtrack-Bell) in accordance with JIS K6217-2.

[0088] <Desorbed gas mass> Thermal desorption mass spectrometry (TDS-MS) was performed using a thermal desorption analyzer TDS-1200 manufactured by Electron Science & Technology Co., Ltd., to measure and analyze the amounts of desorbed methane molecules, methanol molecules, benzene molecules, diphosphorus molecules, and water molecules as follows. In the TDS, the sample stage on which the negative electrode active material was set was made of quartz, and the sample dish was made of SiC. The heating rate was 60°C / min. The heating was controlled by monitoring the surface temperature of the sample. The sample weight was 1 mg, and was corrected by the actual measured weight. A quadrupole mass spectrometer was used for detection, and the applied voltage was 1000V. The amount of each gas (μmol / g) desorbed from inorganic or composite particles was measured by TDS as the temperature increased from 80°C to 1400°C. The mass numbers [M / z] used in the analysis of the measured values ​​were 15 for CH4, 18 for H2O, 31 for CH3OH, 62 for P2, and 78 for C6H6, and the gases corresponding to the above mass numbers were all considered to be the above substances. Here, for the amount of H2O gas, only the integrated value from 80°C to 200°C was used from the results over the entire temperature range, and this was taken as the amount of desorbed H2O (MS2).

[0089] <Maximum endothermic peak temperature> The maximum endothermic peak temperature of the endothermic particles was confirmed by increasing the temperature at a rate of 5 K / min using a differential scanning calorimeter (DSC, Hitachi High-Tech Science Corporation) in accordance with the JIS K7121 standard, and confirming the peak endothermic decomposition temperature.

[0090] <Check for heat generation below 150℃ when endothermic particles and electrolyte coexist> 2.0 mg of endothermic particles and 0.5 mg of the same electrolyte used in producing the secondary battery cell were placed in a dedicated sealed container and crimped, and then the endothermic peak was measured as described above to check for the presence or absence of an exothermic peak below 150°C. In Comparative Examples 1 to 10, a clear exothermic peak was observed near 100°C, but in Examples 1 to 7, this exothermic peak was not observed.

[0091] <Volume density and powder resistance at 60MPa pressure> Using Nitto Seiko Analytech Co., Ltd. MCP-PD51, the volume density of the powder compressed with a hydraulic press from endothermic particles packed in a cylindrical cylinder and the volume resistivity of the compressed powder were measured. The measurement conditions were as follows: Load: 18.85kN Electrode spacing: 3.0mm Electrode radius: 0.7mm Sample radius: 10.0 mm Probe used: 4-point probe

[0092] <Raman spectroscopy> Each endothermic particle was measured using a JASCO Corporation NRS-5100 laser Raman microspectrometer at an excitation wavelength of 532.36 nm under the following measurement conditions: Exposure time: 10 seconds Number of times: 20 Diffraction grating: 300 lines / mm (600 nm) Curve fitting was performed on the spectrum from 800 cm-1 to 3500 cm-1 of the entire measured Raman spectrum, and the peak area (A D ) and 1580cm -1 The area of ​​the peak near G ) ratio (A D / A G ), 2680cm -1 The peak half-width (G'-FWHM) around the peak was obtained.

[0093] [Evaluation of secondary batteries] <Cycle characteristics> The secondary battery cells prepared in Examples 1 to 7 and Comparative Examples 1 to 10 were charged at a constant current of 0.1 CA to 4.3 V of the design capacity in a thermostatic chamber at 25 ° C., and then charged at a constant voltage of 0.05 CA at 4.3 V. Thereafter, constant current discharge was performed at 0.1 CA to 3.0 V. Furthermore, in a thermostatic chamber at 25 ° C., one cycle of constant current charging at 0.2 CA, constant voltage charging at 0.05 CA, and constant current discharging at 0.2 CA was performed under the conditions of a charge end voltage of 4.3 V and a discharge end voltage of 3.0 V, and the initial discharge capacity was measured. The secondary battery cells were subjected to a life test of 100 cycles of constant current charging at 0.5 CA, constant voltage charging at 0.05 CA, and constant current discharging at 0.5 CA under the conditions of a charge end voltage of 4.3 V and a discharge end voltage of 3.0 V at a temperature of 45 ° C. After 100 cycles, the discharge capacity was measured at a constant current charge of 0.2 CA, a constant voltage charge of 0.05 CA, and a discharge of 0.2 CA, and divided by the initial discharge capacity to calculate the capacity retention rate after 100 cycles.

[0094] <Heating test> The secondary battery cells prepared in Examples 1 to 7 and Comparative Examples 1 to 10 were charged at a constant current of 0.1 CA, which is the design capacity, to 4.42 V in a thermostatic chamber at 25 ° C., and then charged at a constant voltage of 0.05 CA at 4.42 V. Thereafter, constant current discharge was performed at 0.1 CA to 3.0 V. Furthermore, in a thermostatic chamber at 25 ° C., constant current charging was performed at 0.2 CA, constant voltage charging at 0.05 CA, and constant current discharging at 0.2 CA under the conditions of a charge end voltage of 4.42 V and a discharge end voltage of 3.0 V, and then the cell was charged at a constant current / constant voltage again to 4.3 V to be used as an initial cell. This secondary battery cell was left in a thermostatic chamber heated to 165 ° C. for 1 hour, and the case where the battery voltage became 4.3 V or less was regarded as "abnormal occurrence", and the abnormality occurrence rate of 10 battery tests was evaluated.

[0095] <Nail insertion test> For the initial cells described above, a nail penetration test was conducted by inserting a 3mm diameter nail (made of stainless steel or soft iron) into the center of the cell at a speed of 50mm / s. If the external temperature of the battery reached 50°C or higher 5 seconds after the nail was inserted, this was deemed to be an "abnormality," and the rate of abnormality occurrence was evaluated for 10 tested batteries.

[0096] <Overcharge test> The initial cell described above was further charged at a constant current of 3 CA up to 12 V. If the external temperature of the battery after 10 minutes of constant voltage charging after reaching 12 V reached 50°C or higher, this was deemed to be an "abnormality." The abnormality occurrence rate of the 10 tested batteries was evaluated.

[0097] <Evaluation Results> The types, properties and locations of the inorganic particles or composite particles used in the above-described Examples and Comparative Examples are shown in Table 1. In addition, the evaluation results for the secondary battery cells of Examples 1 to 7 and Comparative Examples 1 to 10 are summarized in Table 2.

[0098] [Table 1]

[0099] [Table 2]

[0100] <Considerations on Examples and Comparative Examples> From the results in Table 2, in Examples 1 to 7, the occurrence rate of abnormalities caused by temperature rises inside the battery could be sufficiently reduced, even under high temperature conditions, conditions where the internal temperature of the battery is likely to rise, such as external impacts such as nail insertion, and overcharging, compared with Comparative Examples 1 to 10. From these results, it can be seen that the composite particles, which are heat-absorbing particles according to the present invention, were able to sufficiently reduce the internal temperature of the nonaqueous electrolyte secondary battery containing these composite particles. Furthermore, in Examples 1 to 7, even though the composite particles of the present invention are contained in the positive electrode or negative electrode, the cell resistance is suppressed to 1.5 or less, which is equivalent to or lower than that of Comparative Example 1, which does not contain composite particles. Furthermore, from the results of each example, it was confirmed that the same effect was achieved even when the type or amount of raw material used for modification with phosphonic acid was changed, or when the location where the composite particles were contained was changed.

[0101] In contrast, in Comparative Example 2 containing only acetylene black particles, the cell resistance is small, but the effect of reducing the rate of abnormality occurrence is not achieved. In Comparative Example 3 or Comparative Example 5, in which a metal hydroxide that had not been modified was used, the rate of abnormality occurrence was not sufficiently suppressed, and the cell resistance also increased.

[0102] In addition, in the case of Comparative Example 4, in which composite particles that had not been modified were used, the cell resistance was kept low, but the occurrence rate of abnormalities was high, demonstrating that the degree of modification of the composite particles by the modification treatment is important. Moreover, in the case of Comparative Example 6, in which pseudo-boehmite whose degree of modification was adjusted to an optimal range by a modification treatment was used, the abnormality occurrence rate was kept sufficiently low, but it was found that the cell resistance became high.

[0103] In the cases of Comparative Examples 7 to 10, which used a particle mixture in which metal hydroxide particles after the modification treatment were mixed with conductive particles, the results were inferior to those of Examples 1 to 7 in terms of both the cell resistance and the effect of reducing the rate of abnormality occurrence. This shows that the effect of the present invention, that is, the increase in cell resistance can be suppressed and the rise in internal temperature can be sufficiently suppressed, only by forming composite particles in which the particles are bonded to each other, rather than simply mixing metal hydroxide particles with conductive particles, can the effect of the present invention be exhibited.

Claims

1. A composite particle containing a metal hydroxide particle and a conductive particle, Volume resistivity at 60 MPa pressure is 0.1 Ωcm or more 4×10 4 Ωcm or less, The endothermic heat amount at 50°C to 250°C in differential scanning calorimetry is 150 J / g or more and 500 J / g or less, Desorption P from 80 to 1400°C using a temperature programmed desorption mass spectrometer (TDS-MS) 2 Amount (MS1) is 300 x 10 -6 mol / g or more 3000×10 -6 mol / g or less.

2. Desorption of H from 80 to 200°C using a temperature programmed desorption mass spectrometer (TDS-MS) 2 O amount (MS2) is 100 x 10 -6 mol / g or more 1500×10 -6 2. The composite particle for a nonaqueous electrolyte secondary battery according to claim 1, wherein the desorbed gas amount ratio (MS1 / MS2) satisfies the following formula (1): 0.5≦(MS1 / MS2)≦5.0 (1)

3. 1350 cm measured by Raman spectroscopy -1 The peak area (A D ) and 1580 cm -1 The peak area (A G ) ratio (A D / A G ) is 0.5 or more and 3.5 or less, 2680 cm measured by Raman spectroscopy -1 The half-width (G'-FWHM) of the peak near 60 cm -1 More than 150cm -1 The composite particles for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein:

4. The specific surface area (BET1) of the composite particles calculated based on the adsorption isotherm measured by adsorbing water vapor is 8 m 2 / g or more 600m 2 / g or less, The specific surface area (BET2) of the composite particles calculated based on the adsorption isotherm measured by adsorbing nitrogen is 8 m 2 / g or more 600m 2 The composite particles for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein the molecular weight of the composite particles is 1 / g or less.

5. The composite particles for a non-aqueous electrolyte secondary battery according to claim 4 , wherein a specific surface area ratio (BET1 / BET2) satisfies the following formula (2): 0.2≦(BET1 / BET2)≦5.0 (2)

6. CH desorption from 80 to 1400 °C using a temperature programmed desorption mass spectrometer (TDS-MS) 4 Amount (MS3) is 30 x 10 -6 mol / g or more 1000×10 -6 mol / g or less, CH desorption from 80 to 1400 °C by TDS-MS 3 OH amount (MS4) is 10 x 10 -6 mol / g or more 3000×10 -6 The composite particles for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein the molecular weight of the composite particles is 100 mol / g or less.

7. Desorption of C from 80 to 1400°C by TDS-MS 6 H 6 Amount (MS5) is 1 x 10 -6 mol / g or more 4000×10 -6 The composite particles for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 6, wherein the molecular weight is 100 mol / g or less.

8. 8. The composite particles for a non-aqueous electrolyte secondary battery according to claim 1, wherein the metal hydroxide is at least one selected from the group consisting of aluminum hydroxide and kaolinite.

9. 9. A positive electrode for a non-aqueous electrolyte secondary battery comprising the composite particle for a non-aqueous electrolyte secondary battery according to claim 1 in an amount of 0.1% by weight to 5.0% by weight.

10. 9. A negative electrode for a non-aqueous electrolyte secondary battery comprising the composite particle for a non-aqueous electrolyte secondary battery according to claim 1 in an amount of 0.1% by weight to 5.0% by weight.

11. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte solution, 10. A non-aqueous electrolyte secondary battery, wherein the positive electrode is the positive electrode for a non-aqueous electrolyte secondary battery according to claim 9.

12. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte solution, A non-aqueous electrolyte secondary battery, wherein the negative electrode is the negative electrode for a non-aqueous electrolyte secondary battery according to claim 10.

13. A step of mixing raw materials of metal hydroxide particles and conductive particles while heating them to form composite particles of metal hydroxide particles capable of absorbing heat and conductive particles by an endothermic reaction; and modifying the composite particles with a treating agent containing at least one acid selected from the group consisting of phosphoric acid, phosphonic acid and phosphinic acid.

14. The method for producing composite particles for a non-aqueous electrolyte secondary battery according to claim 13, wherein the raw material of the metal hydroxide particles and the conductive particles are mixed while being heated by spray drying.

Citation Information

Patent Citations

  • Electrode additive coated with conductive material, and lithium secondary battery comprising the same

    JP2007522619A

  • Battery pack

    JP2010282795A

  • Manufacturing method for positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery using it

    JP2011228062A

  • Electrode material and method for producing the same

    JP2014072090A

  • Lithium ion secondary battery electrode material, method for manufacturing lithium ion secondary battery electrode material, and lithium ion secondary battery

    JP2014107033A